Nicotinic Mitigation of Neuroinflammation and Oxidative Stress After Chronic Sleep Deprivation - Xue, Rong; Wan, Yahui; Sun, Xiaoqian; Zhang, Xuan; Gao, Wei; Wu, Wei (Frontiers in Immunology, 2019)
Sleep deprivation negatively influences all aspects of health. Oxidative stress and inflammatory responses induced by sleep deprivation participate in its adverse effects but the regulatory mechanisms to counteract them remain poorly understood. In mice subjected to sleep deprivation for 7 days, we found activation of microglia and astrocyte accompanied by down-regulation of α7 nicotinic acetylcholine receptor (α7-nAChR) and reduced activation of downstream PI3K/AKT /GSK-3β. These changes occurred with an increase of pro-inflammatory factors, together with reduced levels of anti-inflammatory factors, transcriptor Nrf-2 and anti-oxidant enzyme HO-1. Administration of an α7-nAChR agonist PHA-543613 induced activation of PI3K/AKT/GSK-3β, and reversed changes in pro-inflammatory and anti-inflammatory factors, Nrf-2 and HO-1. These results suggest that stimulation of α7-nAChR reduce neuroinflammation and oxidative stress after chronic sleep deprivation.